"Understanding older patients: Communication as the key step for a comprehensive approach". Issue 3 (March 2020) - Ramello, Monica; Audisio, Riccardo A.
Abstract: Patient's frailty, attitude, life expectancy, affect the decision-making process, impacting on the following four points: 1.Disclosing the diagnosis. 2.Discussing treatment options and prognosis. 3.Tailoring treatment. 4.Assisting patients along their recovery. Setting up an open, frank, transparent and informative discussion is the key step in addressing a patient-centered treatment plan. Our recommendations are summarized in the following pages.